Identification of Fauna Diversity from Fishermen's Catches on Depok Beach, Bantul, and Analysis of Its Potential as a Contextual Biology Learning Resource for Senior High School Phase E - Nur Al-Azizah Al-Hilmiyah; Sofia Ery Rahayu; Erni Yulianti (Journal of Educational Sciences, 2026)
Biology learning in senior high schools still relies heavily on textbooks and has not optimally utilized local environmental resources as contextual learning materials. Therefore, identifying local biological potential is important to support the implementation of contextual learning in the Merdeka Curriculum. This study aimed to identify the diversity of fauna caught by fishermen at Depok Beach, Bantul, and analyze its potential as a contextual biology learning resource for Phase E. A qualitative descriptive approach with an exploratory design was employed. Data were collected through observation, semi-structured interviews, documentation, and literature review. The feasibility of the identified fauna as learning resources was analyzed based on content relevance, pedagogical value, and contextuality. The results showed that fishermen’s catches consisted predominantly of fish, crustaceans, and mollusks with diverse morphological characteristics and ecological roles. These fauna are relevant to Biology topics, including biodiversity, classification, ecosystems, and ecological interactions. In addition, they possess strong contextual value because they originate from students’ surrounding environment and can be integrated into inquiry-based and field-based learning activities. Therefore, the fauna diversity of Depok Beach has the potential to serve as a feasible contextual biology learning resource and provide a foundation for developing teaching materials based on local coastal potential.